Analysis of Banking Cessie, Novation and Subrogation From The Perspective of Civil Law - Iin Selvina; Tjempaka, Tjempaka (Dinasti Research, 2024)
In daily life, banks play an important role as providers of funds in society. One of the facilities utilized in banking is credit. Funds provided in credit facilities represent bank assets with very high risk. Therefore, to mitigate the risk of non-performing loans, the bank will examine the debtor before the credit facility is granted, then a credit agreement will be made. Credit agreements can be terminated through payment or novation. However, in response to legal events, banks also recognize the existence of subrogation and cessie systems to manage risks. The findings of this study elucidate that, under the Civil Code, all forms of agreements must adhere to the terms of the agreement and principles such as pacta sunt servanda, consensualism, and freedom of contract. Despite the numerous patterns and variations in banking systems and facilities, adherence to positive law is imperative to ensure legal certainty and security for all parties involved.